Design and Development of a Digital Library System Using PHP For Optimizing Library Services at SMK Negeri 1 Luragung - Hafizh Alvian Nazhif; Ipan Ripai (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study aims to develop a PHP-based digital library system as a solution to the conventional library service problems at SMK Negeri 1 Luragung. The existing manual processes for borrowing and returning books make it difficult to track collections accurately and reduce overall operational efficiency. To address these issues, this research adopts a Research and Development (R&D) model using the ADDIE approach, which consists of five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, library needs and user problems were identified. The design stage involved creating system flowcharts, database structures, and interface mockups. During development, a web-based application was built using PHP and MySQL with key features such as member management, book collection management, borrowing and returning modules, and QR code integration for faster transactions. The system was then implemented and tested with actual users. The evaluation was carried out using the Usability (USE) Questionnaire, focusing on usefulness, ease of use, ease of learning, and user satisfaction. The results showed significant improvements in accessibility, transaction efficiency, and overall user experience. Based on these findings, the developed system is considered feasible and highly suitable for implementation as a digital solution for school library management.